Pengaruh Vitamin D3 Terhadap Kadar Hemoglobin Tikus Wistar yang Dipapar Asap Rokok - Hetti Rusmini; Dita Fitriani; Dessy Hermawan; Diah Adelia Emilda (ARTERI : Jurnal Ilmu Kesehatan, 2019)
Hemoglobin is a tetrametric erythrocyte protein that carries O2 to the tissues and returns CO2 and protons to the lungs. Cigarette smoke is proven that could reduce hemoglobin levels through oxidative stress which causes the erythrocyte membrane to be easily lysed. The lysis erythrocyte membrane causes hemoglobin levels to be low. Vitamin D is included in natural antioxidants which have a neuroprotective tendency through antioxidative mechanisms. To determine the effect of giving vitamin D3 on hemoglobin levels in white rats (Rattus norvegicus) male Wistar strain after being exposed by cigarette smoke. This type of pure experimental research (tue-experiment) used pre and post with control group design. Samples were white rats (Rattus norvegicus) male Wistar strain aged 10-12 weeks with the weight of around 150-200 grams in a total of 24 individuals. Samples were divided into four groups including K1 which is not exposed by cigarette smoke and not given of vitamin D3, K2 is a group exposed by cigarette smoke but not given of vitamin D3, K3 is a group that is not exposed by cigarette smoke but given of vitamin D3 a dose of 0.2 µgr /head, P1 is a group exposed by cigarette smoke and given a vitamin D3 dose of 0.2 µgr /head. The test of paired t-test showed a significant difference p <0.05 in the K2 group with p = 0.044, the K3 group with p = 0.013, and P1 group with p = 0.037. Whereas in group 1 there was no significant difference p = 0.932. The One-way Anova test obtained results with a value of p = 0.027 (p <0.05) which means that there were significant differences between groups. The Post Hoc LSD test showed a significant difference in group 1 whit group 2 p = 0.025 and in group 2 with group 3 p = 0.012.